Trends of open innovation in developing nations : contexts of SMEs - Rahman, Md. Hakikur (2011)
Evidently, innovation is a genuine reality within the entrepreneurships, given the circumstances of economic crisis, global competition, and novelties of technologies. Perplexing further to face the reality and overcome crises, enterprises are day by day adopting newly developed ideas, concepts, and perceptions to fit into the scenery of business dimension from within and outside the boundaries of their entities, thus channeling the entrepreneurships through the paradigm of open innovation. By far, the majority of the corporate businesses and multi-national enterprises are competing or collaborating with a consensus to promote value-added products, processes, or services. Notwithstanding, they are transforming the entire entrepreneurship infrastructure to face the reality and move ahead. A major portion of the business community, despite their justified contribution to economic growth and generation of employment, the sector belonging to the small and medium enterprises (SMEs), however, are not always in advantageous situations in the arena of open innovation due to many factors, seen, unseen, attended, un-attended, researched, and deserving of further research. To move further into the context of this research, it has been observed that countries ranking as developed economies are ahead in the race, adopting open innovation in their business development, while countries within the developing and transitional economies are struggling to fit into the race of the champions. This study, though not a specific case of one country, has tried to illustrate a few discrete scenarios from five developing countries through horizontal literature review. The chapter has tried to profile within the format of the casebook, providing generic context of innovation (and open innovation) in those randomly selected countries, presented challenges they are facing, including some recommendations, before concluding for further extensive research.